ЖАНРОВЫЕ ПАРАМЕТРЫ СТРАТЕГИИ КАК ДОКУМЕНТА ДОЛГОСРОЧНОГО ПЛАНИРОВАНИЯ - Bystrova, Aleksandra S (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serii͡a︡ 2, I͡A︡zykoznanie., 2017)
The article characterizes the role of business communication in modern society and, in particular, the role of strategic planning documents, their impact on the public consciousness. The analysis of the strategy identifies the function of the document, composition and speech peculiarities of the text. The author demonstrates the possibility of using the genre approach to the description of compositecontent structure of the document text and using a model of the speech genre as a linguistic technology of its analysis. Using the example of genre of strategy, the author discusses the features and linguistic means of representing the basic genre elements in the document text. These elements compose the model of speech genre and reflect the interaction of extralinguistic factors and linguistic material: communicative purpose, author's image, addressee's image, image of the past, vision of the future, type of dictum content, linguistic embodiment. It is proved that the communicative purpose, associated with the idea of the document's author, and the image of the future are fundamental components of the genre of strategy. Based on the complex of considered parameters in their interaction, especially their verbal expression, the strategy is defined as the genre of the document of long-term planning, which performs an informative and appellative function; it is noted that wide representation and the variety of language means of expressing the vision of the future in combination with the explicit intentions of the strategy's author determine the futurality of the text.